2023
DOI: 10.1002/rnc.6634
|View full text |Cite
|
Sign up to set email alerts
|

Design of a robust model predictive control for nonlinear switched systems: A low‐conservative and recursive feasibility strategy

Abstract: This article proposes a robust H∞ based model predictive control scheme for Lipschitz nonlinear switched systems with persistent dwell time. In the developed method, the constraints corresponding to the recursive feasibility are included and the recursive feasibility is guaranteed. In this scheme, the existence of unstabilizable sub-systems and exogenous disturbances are included which makes it possible to avoid considering an ideal and simplistic assumption about switched systems. By simultaneously designing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Due to the important role in switched systems, switching rules have attracted the attention of many scholars 8,9,10,11 . So far, numerous research results have been reported on various switched systems including variable order fractional switched systems 12 , networked switched systems 11,13 , nonlinear switched systems 14 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important role in switched systems, switching rules have attracted the attention of many scholars 8,9,10,11 . So far, numerous research results have been reported on various switched systems including variable order fractional switched systems 12 , networked switched systems 11,13 , nonlinear switched systems 14 and so on.…”
Section: Introductionmentioning
confidence: 99%